LAW ENFORCEMENT BY THE SABHARA FUNCTION AGAINST THE CRIME OF SELLING ALCOHOLIC BEVERAGES WITHOUT A PERMIT IN THE JURISDICTION OF WONOGIRI POLICE - Irfan Maulana Putra; Hanuring Ayu; Yulian Dwi Nurwanti (Journal of International Islamic Law, Human Right and Public Policy, 2026)
This study aims to analyze law enforcement against the crime of selling alcoholic beverages without a permit in the jurisdiction of the Wonogiri Police and to identify the obstacles faced by law enforcement officers in its implementation. This study uses a normative juridical method with descriptive-analytical research specifications. Data were obtained through literature review supported by interviews and observations of police duties, particularly the Sabhara Function of the Wonogiri Police. The results show that law enforcement against the sale of alcoholic beverages without a permit has been carried out through preventive and repressive measures, including routine patrols, public order operations, raids, inquiries, and investigations of violators. Nevertheless, the effectiveness of law enforcement still faces several obstacles, including hidden and mobile sales practices, limited personnel and supporting facilities, low public legal awareness, and difficulties in proving the administrative status of businesses that lack clear legality. Therefore, stronger synergy among the police, local government, business actors, and the community is needed to improve the effectiveness of supervision and law enforcement against the circulation of alcoholic beverages without permits in order to realize public order, security, and legal protection for the community.